2021
DOI: 10.1021/acs.jcim.1c00056
|View full text |Cite
|
Sign up to set email alerts
|

MHCEpitopeEnergy, a Flexible Rosetta-Based Biotherapeutic Deimmunization Platform

Abstract: As non-"self" macromolecules, biotherapeutics can trigger an immune response that can reduce drug efficacy, require patients to be taken off therapy, or even cause life-threatening reactions. To enable the flexible and facile design of protein biotherapeutics while reducing the prevalence of T-cell epitopes that drive immune recognition, we have integrated into the Rosetta protein design suite a new scoring term that allows design protocols to account for predicted or experimentally identified epitopes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…In this study, we noted that Roxadustat + oral iron was associated with fewer adverse reactions, indicating that Roxadustat + oral iron may have a good safety profile. e possible explanation is that HIF-PHI can effectively promote the production of endogenous EPO in patients, thereby accelerating the production of red blood cells in patients, and mitigating the symptoms of anemia in patients [21][22][23]. In traditional Chinese medicine, the etiology and pathogenesis of renal anemia in CKD is mainly "kidney deficiency with damp-heat and blood stasis," and the lesions are mainly located in the spleen, kidney and liver.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we noted that Roxadustat + oral iron was associated with fewer adverse reactions, indicating that Roxadustat + oral iron may have a good safety profile. e possible explanation is that HIF-PHI can effectively promote the production of endogenous EPO in patients, thereby accelerating the production of red blood cells in patients, and mitigating the symptoms of anemia in patients [21][22][23]. In traditional Chinese medicine, the etiology and pathogenesis of renal anemia in CKD is mainly "kidney deficiency with damp-heat and blood stasis," and the lesions are mainly located in the spleen, kidney and liver.…”
Section: Discussionmentioning
confidence: 99%
“…recently developed a Rosetta-based platform to deimmunize therapeutic proteins. 108 They incorporated a new score term utilizing predicted or experimentally identified T-cell epitope information into the scoring function so that computational protein design calculations can be guided based on the epitope information as well as the energetic stability.…”
Section: Computational Developability Assessment Using Biopharmaceutical Informaticsmentioning
confidence: 99%
“…(1) We develop CAPE-XVAE, a novel machine learning (ML)-based approach combining the abilities of Variational Autoencoders (VAEs) and language models (LMs) with reinforcement learning (RL), to generate MHC-I immune-visibility modified protein sequences. (2) We modify the existing physics-based approach from Yachnin et al [6] that uses the Rosetta Packer [9,10] in a novel fashion to enable it to reduce or increase MHC-I immune-visibility. We call this CAPE-Packer.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bootwala et al [5] demonstrated substantial reduction in binding to murine, rabbit, and human polyclonal antibodies. Another strategy for minimizing antibody visibility is employed by Yachnin et al [6], wherein they aim to decrease the presentation of MHC Class II (MHC-II) epitopes that are crucial for B-cell activation.…”
Section: Introductionmentioning
confidence: 99%